Proceedings Universiti Malaysia Terengganu 8th International Annual Symposium on Sustainability Science and Management (UMTAS 2009), May 3rd-4th 2009 : managing human, environment and natural resources for sustainability - Universiti Malaysia Terengganu International Annual Symposium on Sustainability Science and Management (8th : 2009 : Kuala Terengganu) (Kuala Terengganu : Penerbit Universiti Malaysia Terengganu, 2009)
Includes bibliographical references